2018
DOI: 10.21107/jps.v5i2.4551
|View full text |Cite
|
Sign up to set email alerts
|

Students Misconception: The Developing of Socratic Dialogue Media on Temperature and Heat

Abstract: <em>This purpose of this study is to improve media of Socratic dialogue that has been developed by the previous researcher and to determine the effect of the Socratic dialogue in enhance understanding of heat concept. As a result of prior research, showed students still have a misconception. Data collected from one institution of high school in Malang City using pre and posttest. Student’s conceptual changes that occur previous, during, after will be analyzed based on pretest and posttest scores and reth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The design used is a sequential explanatory design. This design prioritizes quantitative methods, which are the source of measurable data, then qualitative data to strengthen the results of quantitative data by conducting interviews (Maison et al, 2022;Onwuegbuzie et al, 2011;Sujito & Pebriana, 2018). Qualitative research is research that is descriptive and tends to use analysis (Darmaji et al, 2023;Hoeber & Shaw, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The design used is a sequential explanatory design. This design prioritizes quantitative methods, which are the source of measurable data, then qualitative data to strengthen the results of quantitative data by conducting interviews (Maison et al, 2022;Onwuegbuzie et al, 2011;Sujito & Pebriana, 2018). Qualitative research is research that is descriptive and tends to use analysis (Darmaji et al, 2023;Hoeber & Shaw, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The research design used is Correlational. Quantitative research uses statistical analysis in the form of numbers (Sujito, S. et al, 2018). Quantitative research also explains correlation, where this correlational research aims to see the relationship between the independent and dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…This research aims to explore the CT skills of madrasah students. Several studies have revealed students' difficulties in mastering the topic of temperature and heat (Etikamurni et al, 2020;Parno et al, 2020;Priyadi et al, 2019;Sujito et al, 2018;Sukarelawan et al, 2021;Yeo et al, 2021). These difficulties are caused by several factors, including that students must activate concepts related to temperature and heat (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%